Statistics of rainfall rate at 60 minutes integration time in Malaysia - Sobli, Nuurul Hudaa; Ismail, Ahmad Fadzil; Md Isa, Farah Nadia; Mansor, Hasmah; Za'bah, Nor Farahidah; Abdul Malik, Noreha (INSI Publications, 2014)
Background: This paper presents the statistics of rainfall at 60- minute integration time in Malaysia for the period of 12 months from January to December 2009. Objective: To analyze the statistics and characteristics of rainfall intensity measurement at KLIA, Malaysia. To study the behavior of measured rainfall intensity and represent the annual distribution of the measured rainfall through cumulative distribution functions together with different types of rainfall that occurred in 2009. Results: The results obtained show the cumulative distribution functions and amount of the rainfall rate for that particular year. The results also show the different cumulative distribution functions for four different rainfall types that occur in 2009. Conclusion: The study of the 12-month tipping bucket data has given the characteristics of the collected rainfall. From the results obtained, it shows that Malaysia is within equatorial region with the characteristics of two distinguishable rainfall rates that occurs during the whole year.